2019
DOI: 10.1016/j.celrep.2019.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Baroreceptors Sense Blood Pressure through Decorated Aortic Claws

Abstract: Mechanosensory neurons across physiological systems sense force using diverse terminal morphologies. Arterial baroreceptors are sensory neurons that monitor blood pressure for real-time stabilization of cardiovascular output. Various aortic sensory terminals have been described, but those that sense blood pressure are unclear because of a lack of selective genetic tools. Here, we find that all baroreceptor neurons are marked in Piezo2-ires-Cre mice and then use genetic approaches to visualize the architecture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 36 publications
2
87
0
Order By: Relevance
“…Drosophila Piezo was previously shown to confer mechanically activated currents when expressed in human cells and to mediate mechanical nociception ( Coste et al, 2012 ; Kim et al, 2012 ). Furthermore, vertebrate Piezo homologs play diverse mechanosensory roles, including in internal sensation of airway volume and blood pressure ( Min et al, 2019 ; Nonomura et al, 2017 ; Zeng et al, 2018 ). We hypothesized that Drosophila enteric neurons that express Piezo and innervate the anterior gut might mediate volumetric control of appetite.…”
Section: Resultsmentioning
confidence: 99%
“…Drosophila Piezo was previously shown to confer mechanically activated currents when expressed in human cells and to mediate mechanical nociception ( Coste et al, 2012 ; Kim et al, 2012 ). Furthermore, vertebrate Piezo homologs play diverse mechanosensory roles, including in internal sensation of airway volume and blood pressure ( Min et al, 2019 ; Nonomura et al, 2017 ; Zeng et al, 2018 ). We hypothesized that Drosophila enteric neurons that express Piezo and innervate the anterior gut might mediate volumetric control of appetite.…”
Section: Resultsmentioning
confidence: 99%
“…Stimuli that differ in these features represent different body changes. For example, stretching the arterial wall implicates an increase in blood pressure, whereas stretching the stomach wall signals food ingestion 15 , 20 . Similarly, the same bioactive signal (such as serotonin) released from different tissue layers within the intestine communicates different organ information to the brain 21 .…”
Section: Mainmentioning
confidence: 99%
“…mCherry: "end-net" endings that showed thin and long "free" nerve endings and "discoid or club" endings, where terminals stopped abruptly with an enlargement ( Figure 2D). These specialized nerve terminals have been described as baroreceptors in the aortic arch in rats and mice (36)(37)(38)(39). Ensemble images of the cross section of the whole aorta showed that TTN3 + fibers encircled the entire aorta ( Figure 2E).…”
Section: Resultsmentioning
confidence: 82%